New Plain 200 Epoxy Based Carbon Prepregs. (2017) - Modrea, Arina; Szava, Renata; Niculita, Camelia; Scutaru, Maria Luminita
Abstract: This paper presents the most important mechanical properties of three new developed prepregs based on 1050 epoxy resin and PLAIN 200 carbon fabric with 200 g/m 2 specific weight used as skins in ultra-lightweight sandwich composite panels with applications in the aerospace industry. Three types of prepregs using one ply, two respective three plies carbon fabric have been developed and then cured in an autoclave with controlled pressure and temperature. From cured plates with 0.2, 0.4 and 0.6 mm thickness, eight specimens from each plate have been cut using a special diamond tool and subjected to tensile tests until break. Various distributions have been experimentally recorded including stress-strain, Young's moduli, load at break-machine extension at break, tensile strengths as well as mean values distributions in case of these three prepregs. Young's modulus, stress and percentage strain at maximum load, force at break, stiffness and tensile strength present an increased tendency with the increase of plies number unlike strain at maximum extension, which presents a decreased distribution with the increase of plies number.